Pioneering COVID-19 Pandemic Partnerships: Federally Qualified Health Centers and Geriatric Workforce Enhancement Programs Work Together to Care for Diverse Underserved Older Adults. (September 2022) - Gibbs, Lisa; Rousseau, Julie; Tumosa, Nina; Gupta, Roopali; Olsen, Bonnie; Faul, Anna; Reichstadt, Jennifer; Cotton, Samantha; Sivers-Teixiera, Theresa; Saville, Neika; Lee, Jung-Ah
Background: The COVID-19 pandemic disproportionately affected populations served by Federally Qualified Health Centers (FQHCs), with high morbidity and mortality rates in ethnic minority older adults. In response to this pandemic, academic geriatric medicine teams through federally funded Geriatric Workforce Enhancement Program (GWEP) with FQHC partnership implemented new initiatives to improve the care for vulnerable older adults.Objectives: To describe how four FQHC/GWEP teams collaborated in caring for diverse communities of older adults during the pandemic.Methods: Four GWEPs have addressed pandemic response efforts with their respective FQHC partners. These collaborations to meet the increasing numbers of older adults seeking services, and the rising disparities exacerbated during the pandemic are delineated.Results: FQHC/GWEP partnerships enabled access to care, whether in-person or virtually to serve unmet needs of underserved older adults during the pandemic. Partnerships promoted COVID-19 education, testing, and vaccinations. Most FQHCs faced severe staffing shortages, and the digital divide challenged patients with barriers. GWEPs provided direct care, created educational materials, and developed telehealth programs. These partnerships addressed social determinants of health gaps caused by the pandemic.Conclusion: The findings demonstrate that strong partnerships between GWEPs and FQHCs mitigate health inequities for vulnerable ethnic minority and rural older adults during pandemic crises.